Self-Publishing, Vanity Publishing and Indie Publishing: A Shortcut to Fame or A Dangerous Game? - Widjati Hartiningtyas (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2023)
In November 2022, a Twitter account reported fraud committed by an owner of a well-known vanity publisher. The post that was retweeted thousand times revealed that many authors experience the same thing. Based on that case, this study analyzed reasons that drive authors to self-publish or use vanity and indie publishing service. To answer the research question, the researcher conducted semi-structured interviews with five authors acting as informants. The researcher presents the interview's results in three categories: the romanticism of publishing printed books, idealism in writing, and the prestige of indie publishing. The researcher analyzes the data using Michael Foucault's thoughts in his essay What is an author? This study found that though the informants used alternative publishing because conventional publishers did not accept their works, they had different reasons to continue using alternative publishing. The informants agreed that alternative publishing offers flexibility that enables them to maintain their idealism. However, the informants had different opinions on the classic conflict between idealism and income. The informants do not consider indie publishing more prestigious than conventional publishers or vice versa. However, they have their considerations when choosing a type of publisher. The interviews also showed that a supporting community, a valuable network, and pieces of information are necessary before using alternative publishing.